Mesenchymal stromal cells loaded with paclitaxel induce cytotoxic damage in glioblastoma brain xenografts. Issue 1 (December 2015) - Pacioni, Simone; D'Alessandris, Quintino; Giannetti, Stefano; Morgante, Liliana; De Pascalis, Ivana; Coccè, Valentina; Bonomi, Arianna; Pascucci, Luisa; Alessandri, Giulio; Pessina, Augusto; Falchetti, Maria; Pallini, Roberto
Abstract Introduction The goal of cancer chemotherapy is targeting tumor cells and/or tumor-associated microvessels with the lowest systemic toxicity. Mesenchymal stromal cells (MSCs) are promising vehicles for selective drug delivery due to their peculiar ability to home to pathological tissues. We previously showed that MSCs are able to uptake and subsequently to release the chemotherapeutic compound Paclitaxel (PTX) and to impair the growth of subcutaneous glioblastoma multiforme (GBM) xenografts. Here we used an orthotopic GBM model1) to assess whether PTX-loaded MSCs (PTX-MSCs) retain a tropism towards the tumor cells in the brain context, and2) to characterize the cytotoxic damage induced by MSCs-driven PTX release in the tumor microenvironment. Methods U87MG GBM cells were fluorescently labeled with the mCherry protein and grafted onto the brain of immunosuppressed rats. In adjacent brain regions, we injected green fluorescent protein-expressing murine MSCs, either loaded with PTX or unloaded. After 1 week survival, the xenografted brain was assessed by confocal microscopy for PTX-induced cell damage. Results Overall, MSCs showed remarkable tropism towards the tumor. In rats grafted with PTX-MSCs, the nuclei of U87MG cells showed changes that are typically induced by PTX, including multi-spindle mitoses, centrosome number alterations, and nuclear fragmentation. Multi-spindle mitoses resulted in multinucleated cells that were significantly higher in tumors co-grafted with PTX-MSCs than in controls. Nuclear changes did not occur in astrocytes and neurons surrounding the tumor. Conclusions MSCs appear particularly suited for anti-neoplastic drug delivery in the brain since PTX-specific damage of GBM cells can be achieved avoiding side effects to the normal tissue.